Understanding Technical Instructors Motivational Practices in Vocational Training Centre, Morang, Nepal - Koirala, Amit; Dhungana, Gita (Journal of Training and Development, 2015)
This study “understanding technical instructor’s motivational practices in vocational training centre, Morang Nepal” tries to explore the motivational and demotivational factors among the technical instructors in vocational training centre, Morang, Nepal. As motivational factors plays an important role in carrying out teaching and learning activities this study tries to understand the key factors that enhance or hinder the technical instructors for teaching in vocational training centre and for carrying out qualitative research, researchers employed case study research design. DOI: http://dx.doi.org/10.3126/jtd.v1i0.13088 Journal of Training and Development Vol.1 2015: 33-37